Community case studies: an interpretative phenomenological analysis on sexual abuse in urban Chennai - Ganesan, Niranjana; Gopalakrishnan, Bhuvaneswari (Frontiers in Psychology, 2024)
This study attempts to explore the lived experiences of sexual abuse during COVID-19 in a big metropolitan city in India, with a special interest in understanding the contemporary problems faced by teenagers. Any Phenomenological enquiry begins with identifying and determining the suitability of the participants. In this case, the participants are teenage girls and boys, who have experienced one or other forms of sexual abuse during the COVID-19 pandemic. By restricting the act of sexual abuse that happened during a pandemic, this research brings attention to the medium (material), social conditions, and the role of the cultural world in the act of sexual abuse. It begins by distributing a questionnaire to 500 participants to identify the participants who had experienced one or other forms of sexual abuse during the aforementioned time. Secondly, brief interviews with the identified participants are conducted to record their lived experience of sexual abuse. Using this collected narrated experience as a reservoir for phenomenological reflection, this research aims to uncover moments of lived experience emphasizing spatial, corporeal, and temporal aspects as well as provide greater depth in understanding sexual abuse in the context of teenage lives. It helps to understand the different forms of sexual abuse experienced by teenagers as well as portrays how space plays a major role in the act. This article aims to highlight the role of the material world in the act as well as how the social, political, and cultural contexts are materialized in the act of sexual abuse. Also, this article analyses how the existing intervention mechanisms support the prevention of sexual abuse in different social settings as well as emphasizes the gaps in the intervention mechanisms apropos the chosen narrative data. To sum up, this study aims to create awareness, provides prevention mechanisms considering the role of the material world, and advocates for SDG 16 (Promote justice, peaceful and inclusive societies) and SDG 5 (Achieve gender equality and empower all women and girls).